Is Malaysia Ready for Human Gene Editing: A Regulatory, Biosafety and Biosecurity Perspective - Kalidasan, V.; Theva Das, Kumitaa (Frontiers in Bioengineering and Biotechnology, 2021)
Gene editing platforms have revolutionized the field of genetics with a direct impact on the public health system. Although there are apparent benefits, it is often accompanied by public debates over its uncertainties and risks. In the Malaysian context, modern biotechnology has raised questions about how to best govern gene editing in regulations, biosafety, and biosecurity. Even though standards and guidelines on stem cell and cell-based therapies have been developed, there are no appropriate legal frameworks available for gene editing yet. Nevertheless, biosafety regulations were established to balance promoting biotechnology and protecting against their potential environmental and human health risks. There is also a need to address the potential of genetically modified organisms (GMOs) as bioweapons. Numerous frameworks from several international organizations may provide valuable input in formulating documents on gene editing. By establishing comprehensive guidelines, legal policies, and standards to tackle the challenges and risks associated with gene editing, Malaysia can successfully apply this modern technology in this country.